Modelling single-effect of Lithium Bromide-Water (LiBr–H2O) driven by an evacuated solar tube collector in Ma'an city (Jordan) case study. (September 2022) - Marashli, Abdullah; Alfanatseh, Enas; Shalby, Mohammad; Gomaa, Mohamed R.
Abstract: The refrigeration systems consume a high amount of energy. In Jordan, conventional energy is an expensive option. Thus, this consumption will be significant. In this work, a mathematical model of the Single-Effect Solar Absorption Cooling system (SESAC), utilizing Lithium Bromide-Water (LiBr–H2 O) as the working fluid, has been developed with evacuated tube collectors. This model has been designed according to the climate in Ma'an, Jordan. The effect of the temperature changing of the cooling system cycle on the coefficient of performance (COP) and the LiBr–H2 O crystallization has been investigated using MATLAB/Simulink environment. The best temperatures at which the system operates without crystallization were defined. Moreover, the effect of improving the heat exchanger solution on the overall system performance has been investigated. The medium cooling capacity was (120 kW) and it runs by 243.3 m 2 evacuated tube solar collectors. It was found that the generator's temperature is the critical factor that affects the system's performance as a whole. The highest value of COP was 0.74, at a generator temperature of 110 °C without crystallization.